Saúde suplementar em disputa: análise da dinâmica institucional do mercado de planos de saúde - Shimomukay, Roseane (Universidade do Vale do Rio dos Sinos, 2025)
The Brazilian supplementary healthcare sector constitutes a contested field, characterized by tensions between economic, social, and political interests. This study, grounded in institutional theory, seeks to understand the dynamics of legitimacy in this market by analyzing its historical trajectory, current structure, and emerging institutional logics. The research identifies three predominant institutional logics — the market logic, the social rights logic, and the state logic — that influence the practices and decisions of sector actors. The findings indicate that the sector's legitimacy is continuously challenged by factors such as the perception of excessive profit-driven focus, the intense growth of judicialization, and questions regarding the effectiveness of ANS regulation. Attacks on the sector's legitimacy undermine trust among stakeholders, requiring strategies that reconcile regulatory pressures, social demands, and ethical practices to sustain the market's normative, cognitive, and regulatory legitimacy. Strategies focused on transparency and consumer education are highlighted as essential for strengthening market trust and promoting greater balance. The theoretical contribution of this study lies in its understanding of the dynamics of legitimation and delegitimation in a contested market influenced by multiple institutional logics and marked by strong regulatory presence. The practical contribution lies in providing insights for the development of institutional and discursive strategies that reinforce the sector’s legitimacy through proposals to mitigate the attacks promoted by identified narratives. Finally, the study of the supplementary healthcare market can support public policies by revealing different perspectives and discourses within the debate.
Keywords: Saúde suplementar; Legitimidade; Teoria institucional; Mercados contestados; Supplementary healthcare; Legitimacy; Institutional theory; Contested markets; ACCNPQ::Ciências Sociais Aplicadas::Administração